PERBANDINGAN NILAI TROMBOSIT, HEMATOKRIT DAN NLR ANTARA PASIEN DBD ANAK DAN DEWASA DI RUMAH SAKIT KHUSUS BEDAH MITRA ARIVA AJIBARANG - Cahya Wulan Puspa Irmawati; Ira Pangesti; Yusuf Eko Nugroho (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Abstract Dengue Hemorrhagic Fever (DHF) is a viral infection caused by the dengue virus that remains a major public health problem in Indonesia, affecting various age groups with different clinical manifestations. Laboratory examinations such as platelet count, hematocrit level, and neutrophil-to-lymphocyte ratio (NLR) are important indicators to assess the severity of DHF. This study aimed to compare the values of platelet count, hematocrit, and NLR between pediatric and adult DHF patients at Mitra Ariva Ajibarang Surgical Hospital. The study used a quantitative method with a total sampling approach involving 40 medical record data of DHF patients from December 2024 to March 2025, consisting of 20 pediatric and 20 adult patients. Data were analyzed statistically using the Shapiro–Wilk test for normality and the independent t-test to examine intergroup differences. The results showed a significant difference (p < 0.05) in all three variables. The mean platelet count was higher in children (90.45×10³/µL) than in adults (62.20×10³/µL), while hematocrit and NLR values were higher in adults (47.05% and 3.56) compared to children (42.15% and 1.77). These findings indicate that adult patients experience more severe thrombocytopenia, hemoconcentration, and inflammatory responses than children. In conclusion, age significantly affects hematological parameters in DHF, with adult patients showing greater disease severity. Routine monitoring of platelet, hematocrit, and NLR values is essential for evaluating disease progression and preventing complications in DHF patients. Keywords: Dengue Hemorrhagic Fever, platelet, hematocrit, NLR, children, adults